Growth, radiation use efficiency and grain yield of wheat as influenced by nitrogen, tillage, and crop residue management. (2nd October 2018) - Akmal, Mohammad; Shah, Asad; Ali, Johar
Abstract: Soil organic carbon (SOC) sequestration is one of the major agronomic measures to mitigate green house gas emission, enhance food security, and improve agriculture sustainability. The study, therefore, aimed to evaluate crop growth (CG) and radiation use efficiency in spring wheat ( Triticum aestivum L.) treated soil with residue type (RT), that is, cowpea ( Vigna unguiculata ) as legume (LR), maize ( Zea mays L.) as cereal (CR) and no residue (NR) treatment applied (5 t ha −1 ) on dry matter basis. The CR was subsequently incorporated with tillage depths (TD), that is, deep (DT = 35 cm) and shallow (ST = 15 cm) as main plot treatments. The N was applied in two splits starting from 0 to 160 kg ha −1 as sub plot treatments. Experiment was conducted in two CG seasons 2009–11 at Agronomy Research Farm, the University of Agriculture Peshawar, Pakistan. Results showed the highest CG and RUE with LR incorporated than CR and/or NR with DT. Increasing N-rate resulted an increase in CG, RUE and biomass of wheat. Residue of LR or CR deeply incorporate into the soil has resulted healthy traits (i.e., tillers- and spikes number), which resulted higher biomass. Nitrogen applied 120 kg ha −1 resulted in higher CG, RUE and grain yield for treatment LR, followed by CR and the lowest for the NR. Crop of second year showed higher grain yield, which was due to healthy traits including better CG and RUE. The study suggests that CR of LR or CR nature incorporated deep into the soil can optimize crop N-fertilizer demand for optimum production, which protects environment from the excessive use of N application.